Reformulasi Pajak Daerah: Penerapan Pajak Pertambahan Nilai Provinsi Di Indonesia - Setiadi Alim Lim (BIP's JURNAL BISNIS PERSPEKTIF, 2013)
In Indonesia, taxes are differentiated on central taxes and local taxes. Central taxes are levied by the central government, while local taxes are levied by the provincial government named as provincial taxes and local taxes which are levied municipal/ regency government called municipal/regency taxes. Partial results of the central government's tax collections will be allocated through transfer method called General Allocation Fund and the Special Allocation Fund to the provincial government and the municipal/regency government. The model used still causes an imbalance in both vertical and horizontal fiscal substantial. In line with a growing decentralization issue reverberating around the world, so one way to reduce the fiscal imbalance is that local governments should be allowed to levy taxes which potential is quite significant. In this regard, it is proposed that the VAT is not only levied by the central government, but also levied by the provincial government as an surtax, and this is the main income of the provincial government. While local taxes that are currently levied by the provincial government will be levied delegated to the municipal/regency government gradually.